Variability of agromorphological traits in Portulaca grandiflora through induced mutation using colchicine - SYARIFAH IIS AISYAH; NUR IZZAH MEININGRUM; YOSHUA SHANDY YUDHA; WARAS NURCHOLIS (Society for Indonesian Biodiversity, 2024)
Abstract. Aisyah SI, Meiningrum NI, Yudha YS, Nurcholis W. 2024. Variability of agromorphological traits in Portulaca grandiflora through induced mutation using colchicine. Biodiversitas 25: 2484-2493. Portulaca grandiflora Hook is an ornamental plant originating from the Portulacaceae family, and it has been extensively cultivated on various continents. P. grandiflora displays appealing flower shapes and vibrant colors suitable for growth in a tropical landscape. Increased morphological diversity carries significant importance in the aesthetic function of ornamental plants. The higher the variation in the morphological characteristics of ornamental plants, the greater the market value of these plants due to their enhanced aesthetic appeal. Additionally, colchicine, a polyploidy-inducing agent, can enhance the plant genetic diversity. This study aims to investigate the impact of colchicine application on the morphological characters of P. grandiflora. The experiment was conducted for four months at the Leuwikopo Experimental Field, IPB, with two factors of Completely Randomized Block Design: The colchicine treatment comprises five concentration levels (0, 0.05, 0.1, 0.15, and 0.2), with four test genotypes: Orange, Peach, Bicolor, and Banana. A significant reduction in growth was observed in the Bicolor genotype, followed by the Banana genotype, indicating varying tissue sensitivities to colchicine treatment. The study reveals variations in morphological responses for each concentration treatment and genotype used. Statistical results confirm aspects: (i) each genotype displays different performance, (ii) the combined treatment of colchicine significantly influences the growth and development of quantitative traits, and (iii) The interaction (colchicine x genotype) was statistically significant for all quantitative characters of P. grandiflora except stem diameter. Qualitative traits, such as morphological changes in stem color, leaf color, and shape, were observed. Three correlation values are positive and statistically significant: plant length and leaf width, number of branches on shoots and leaves, and number of branches on shoots and flowers. Putative mutants of P. grandiflora exhibiting new traits require in-depth exploration in subsequent generations.